STRATEGI MENJALANKAN UJIAN SEKOLAH PADA MASA PANDEMI COVID-19 DI SD CHARITAS 01 BELITANG - Maria Angelina Priyanti (Jurnal PGSD Musi, 2020)
Facing the graduation period of students in the situation and condition of the COVID-19 pandemic, SD Charitas 01 Belitang experienced several obstacles so that the school made alternative strategies for the smooth assessment of the students' final assessment. By implementing the health protocol and Circular No. 4 of 2020, based on advice from the Belitang District Education Office, schools in the Belitang area continue to run the School Examination as an additional assessment for graduation requirements. The research objective is to determine the strategies adopted by schools in dealing with US implementation, determine the readiness of schools in the implementation of US and how schools overcome obstacles facing US implementation during the COVID-19 Pandemic. This research is a qualitative study using descriptive methods. Data collection techniques carried out by interview and triangulated using a questionnaire method. The results of this study, strategies that are based on the Vision and Mission of the school and applied to help students become easier to take the exam. The school also stated that the readiness of the school and students was prepared optimally. However, both the school and students experienced several obstacles during the implementation of the strategy. School Exams held during the COVID-19 Pandemic at Charitas Elementary School 01 Belitang in 2020 could run smoothly as expected.